Facing disabilities in children with prenatal alcohol exposure: parenthood and stressors according to families and professionals' narratives - Simmat-Durand, Laurence; Toutain, Stéphanie (Frontiers in Sociology, 2025)
BackgroundPrenatal alcohol exposure can cause neurodevelopmental disorders affecting children's brain function, educational and social skills throughout their lives. International literature highlights the challenge for families of raising an affected child. Beyond their exposure to alcohol, these children face other negative events such as separation from their biological families, the mental health problems of their parents, and so forth, which will have repercussions on their childhood and their future health.MethodsThis research used semi-structured interviews with 107 participants, namely 53 social and health-care professionals and 54 families (foster, adoptive or biological) of 62 children prenatally exposed to alcohol. All were recruited in two regions and a national association of parents in France. Families were diverse in terms of members, regions, ages, and social and cultural backgrounds. A thematic analysis was performed to distinguish parenthood styles and stressors.ResultsThe analysis allowed identification of three types of parenthood used to cope with these neuro-disabilities, independent of the legal status of the family: first, intensive parenting with a major involvement of the adults in charge; second, inclusive parenting seeking to normalize the child within the siblings, school group or society; and third, distanced parenthood where the disability was down-played and the child considered to have lesser abilities. In all cases, the stress, and the difficulties encountered, have a negative influence on the mental health of the parents and/or on the integrity of the family unit, with different modalities of shared parenting.ConclusionBecoming the parent of a child with disabilities, even more so when the origin is attributed to stigmatized and stigmatizing behavior for both mother and child, is a long process that requires adequate diagnosis and management to avoid loss of opportunity. Parental investment, which determines the family trajectories, is based on social and cultural resources.